Colon Atresia in a Neonatal Piglet - Oliveira, Larissa Almeida; Viana, Isabella Isis Rodrigues; Santos, Ana Luísa Mendes; de Assis, Larissa Florêncio; Nascimento, Laura Gonçalves; Lacreta Junior, Antonio Carlos Cunha; Wouters, Flademir; Coutinho, Adriana de Souza; Toma, Hugo Shisei (Acta Scientiae Veterinariae, 2025)
Background: Intestinal atresias are anomalies that occur during embryonic development and may involve the jejunum, ileum, colon and anus. In swine, these anomalies can affect one or more piglets, presenting varying degrees, and it’s common for them to be present at birth or become evident shortly thereafter. However, establishing a definitive diagnosis can be challenging, as the investigation of perinatal conditions often requires multiple sources of information, especially when the lesions are minimal and knowledge about subsequent events is quite limited. This study aims to report the clinical management, clinical signs, radiographic findings, and necropsy of a case of colonic atresia in a pig. Case: A 10-day-old male pig, a crossbreed between the Large White and Landrace breeds, weighing 1.9 kg, was presented to the Large Animal Veterinary Hospital of the Federal University of Lavras, with a chief complaint of lethargy and abdominal distension. The sow was in its 4th parity and had no history of gestational or parturition problems. The pig was raised in an intensive breeding system and was born in a litter of 14 piglets of uniform weight, none of which showed clinical abnormalities. At birth, the piglet had a good body condition score and alert demeanor. However, on the 8th day of life, abdominal distension, lethargy, and anorexia were observed. On physical examination, the piglet exhibited dyspnea with pronounced abdominal effort, an arched back, and difficulty in movement. The heart rate was 160 beats per minute, respiratory rate 48 breaths per minute, and rectal temperature 37.5°C. The mucous membranes were pink, and pulmonary auscultation revealed coarse crackles and wheezing. Based on clinical signs, intussusception was suspected, and abdominal ultrasonography and radiography were performed. Ultrasound examination revealed a large amount of fluid within the intestines, although no free abdominal fluid or other significant abnormalities were noted. Radiographic evaluation showed an accumulation of intestinal content and gas. Due to the presence of coarse crackles and wheezing, treatment for bronchopneumonia was initiated. The piglet exhibited improvement in respiratory function and resumed milk and water intake but remained unable to defecate. On the 3rd day of treatment, the animal died, and a necropsy was performed. Post mortem examination revealed that the small and large intestines were filled with content, while the final portion of the spiral colon was completely empty. Additionally, an abscess was identified in the spiral colon, along with a congenital atresia affecting the terminal segment of the spiral colon. Discussion: The initial diagnostic suspicion in this case was intussusception; however, it was ruled out during necropsy. The characteristics of colonic atresia in this report were more consistent with a type II classification, as a fibrous remnant connected the 2 ends of the colon. Congenital intestinal abnormalities are rare but can cause significant losses in swine farming. Therefore, they should always be considered in the differential diagnosis of neonatal pigs presenting with abdominal distension and lethargy. Due to the potential hereditary nature of the condition, it is recommended that the parents be removed from breeding to reduce the risk of recurrence in future litters. Further studies on intestinal anomalies in pigs are necessary, as the current literature remains scarce. Keywords: intestinal atresia, bowel, congenital, necropsy, swine. Título: Atresia de cólon em neonato suíno Descritores: atresia intestinal, intestino, congênito, necropsia, suíno.